2011
DOI: 10.21101/cejph.a3684
|View full text |Cite
|
Sign up to set email alerts
|

Health Promoting Behaviours and Lifestyle Characteristics of Students at Seven Universities in the UK

Abstract: SUMMARYAims: University students' wellbeing and health promoting and damaging behaviours are important and comprise many parameters. The purpose of this study was to assess a range of health behaviours and lifestyle characteristics of 3,706 undergraduate students from seven universities in England, Wales and Northern Ireland. We compared differences in these parameters between males and females, and across the participating universities.Methods: A self-administered questionnaire assessed socio-demographic info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
142
3
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(169 citation statements)
references
References 56 publications
11
142
3
8
Order By: Relevance
“…15 Questionnaires were employed to assess participant's lifestyle habits. The questionnaire gained quantitative data using Likert scales (1-10, 1=healthier option and 10=unhealthier option) to measure participants' lifestyle habits, which included variables including diet, sleep pattern, physical activity, mobility, balance, alcohol consumption, tobacco use and well-being, that followed a pre-validated questionnaire similar to that of Ansari et al 1 …”
Section: Data Collectionmentioning
confidence: 99%
“…15 Questionnaires were employed to assess participant's lifestyle habits. The questionnaire gained quantitative data using Likert scales (1-10, 1=healthier option and 10=unhealthier option) to measure participants' lifestyle habits, which included variables including diet, sleep pattern, physical activity, mobility, balance, alcohol consumption, tobacco use and well-being, that followed a pre-validated questionnaire similar to that of Ansari et al 1 …”
Section: Data Collectionmentioning
confidence: 99%
“…Recent studies aimed at comprehending, controlling and monitoring such behaviors point out their high prevalence reflected on sedentary habits, eating disorders, traffic accidents, consumption of tobacco, alcohol and other drugs, and violence against oneself and others. (1)(2)(3)(4)(5) Wang et al observed a high percentage of university students who presented unhealthy lifestyles. The researchers stood up to defend the need for taking social and territorial contexts into account in the preparation of plans toward minimizing the morbidity-mortality loads caused by non-transmissible chronic diseases, as well as the need for improving the quality of life of this population by means of regional development programs of healthcare education that may mitigate social-spatial inequalities.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [18] found similar mean scores for the subscales of HPLP-II with our study among university students in Japan. In contrast, in the United Kingdom, females generally reported more consumption of fruits and vegetables; moreover, male students had a higher level of physical activity, consumed less sweets and had more restful sleep [19]. In a study on a group of students, the highest mean score was reported for interpersonal relationships and stress management and the lowest scores were reported for health responsibility and physical activity [20].…”
Section: Discussionmentioning
confidence: 92%